Insights into the cashew production system in Guinea-Bissau: implications for agroecosystem sustainability - Sierra-Baquero, Paola; Catarino, Sílvia; Costa, Gonçalo João; Barai, Amidu; Correia, Zinha; Ferreira, Maria Rosa; Varón-Devia, Edgar; Romeiras, Maria M.; Catarino, Luís; Duarte, Maria Cristina; Monteiro, Filipa (Frontiers in Sustainable Food Systems, 2024)
Introduction West Africa, particularly Guinea-Bissau, heavily relies on cashew nut (Anacardium occidentale L.) production, which significantly impacts the countries’ economies. Cashew exhibits remarkable adaptability to impoverished and arid soils. Understanding producers’ socio-economic characteristics is crucial due to their potential influence on crop productivity and household income. Methods This study aims to characterize the socio-economic, productive, and phytosanitary aspects of cashew production in Guinea-Bissau, through 151 interviews with producers across all administrative regions of the country. Results Our findings reveal that cashew producers are mainly males aged 40 to 60, they typically manage plantations under 5 ha, with the smaller plantation areas located in Gabú, Cacheu, and Bolama. The age of the older trees averaged 31 years, with the highest age found in Biombo. Tree density averaged 286 trees per hectare, with higher values in Cacheu, Bafatá, and Bolama. Cashew nut yield in 2020 averaged less than 0.5 tons per hectare, with farmer-set prices generally lower than government determined prices. Oio, Tombali, and Bolama were the regions most affected by pests, while Oio and Cacheu (North) were the most affected by diseases. Top pests included termites, branch girdler, weaver ants, African grasshopper, and stem borer; while top diseases comprised gummosis, anthracnose, and dieback. Discussion Characterization of cashew production system is crucial at both national and regional levels to identify region-specific limitations and strengths, aiding in the formulation of tailored strategies for sustainable production. Moreover, cashew production plays a crucial role in household incomes in Guinea-Bissau, underscoring the necessity of developing integrated management strategies.